Phenotypic and Functional Characterization of Monoclonal Antibodies with Specificity for Rhesus Macaque CD200, CD200R and Mincle. - Siddappa N Byrareddy; Dawn Little; Ann E Mayne; Francois Villinger; Aftab A Ansari (PLoS ONE, 2015)
Lectin-like molecules and their receptors are cell surface molecules that have been shown to play a role in either facilitating infection or serving as transporters of HIV/SIV in vivo. The role of these lectin-like molecules in the pathogenesis of HIV/SIV infection continues to be defined. In efforts to gain further insight on the potential role of these lectin-like molecules, our laboratory generated monoclonal antibodies (mAb) against the human analogs of rhesus macaque CD200, CD200R and Mincle, since the rhesus macaques are accepted as the most reliable animal model to study human HIV infection. The characterization of the cell lineages from the blood and various tissues of rhesus macaques that express these lectin-like molecules are described herein. Among the mononuclear cells, the cells of the myeloid lineage of rhesus macaques are the predominant cell lineages that express readily detectable levels of CD200, CD200R and Mincle that is similar to the expression of Siglec-1 and Siglec-3 reported by our laboratory earlier. Subset analysis revealed that a higher frequency of the CD14+/CD16- subset from normal rhesus macaques express CD200, CD200R and Mincle. Differences in the frequencies and density of expression of these molecules by the gated population of CD14+ cells from various tissues are noted with PBMC and bone marrow expressing the highest and the mononuclear cells isolated from the colon and ileum expressing the lowest levels. While a significant frequency of pDCs and mDCs express Siglec-1/Siglec-3, a much lower frequency expresses CD200, CD200R and Mincle in PBMCs from rhesus macaques. The mAb against CD200 and CD200R but not Mincle appear to inhibit the infection of macrophage tropic SIV/SHIV in vitro. We conclude that these mAbs may have potential to be used as adjunctive therapeutic agents to control/inhibit SIV/HIV infection.